An Experience Report on the use of Problem-based learning and Design Thinking in a Requirements Engineering Postgraduate Course - Vilela, Jéssyka; Silva, Carla (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
Context: Education in Requirements Engineering (RE) is fundamental to train professionals capable of dealing with the challenges of the software development. In this sense, methodologies such as Problem-Based Learning (PBL) and Design Thinking (DT) are valuable tools that can be used to prepare students to tackle challenges of the real world. Objective: This paper presents an experience report of a RE graduate course with 21 students that adopted innovative techniques like DT and PBL. Method: We used quantitative and qualitative analysis to determine the strengths and the points of improvement of the applied methodological approach, the benefits and challenges of using DT, the degree of easiness and usefulness of the used techniques from the point of view of the students and also evaluating both the students’ self-reporting and team performance. Results: The most difficult practices/techniques to implement were "partial deliveries of project activities," "crazy 8’s," and "textual specification of use cases." On the other hand, the easiest practices/techniques were "prototype" and "development of requirements document." Regarding usefulness, the analysis indicates that the most useful practices/techniques were "prototype," "use case diagram," "brainstorming," "project presentation," and "collaborative construction of the project." Conversely, the least useful practices/techniques were "validation of requirements using a checklist" and "personas." In general, the results indicate that the teams are constantly evolving, and periodic evaluation can be an important tool for identifying strengths and areas for improvement. Conclusions: The course offered a valuable opportunity for professional development, but there is room for improvement in certain aspects to ensure an even better learning experience for future students. We contribute to the literature by presenting a successful experience of using DT and PBL in a short RE course as well as we discuss some lessons learned and highlight the potential this approach has to improve RE education.